Recent Progress in Preparation and Application of Nano‐Chitin Materials. Issue 4 (22nd June 2020) - Yang, Xuefei; Liu, Jie; Pei, Ying; Zheng, Xuejing; Tang, Keyong
Abstract : Chitin is a kind of natural macromolecule material which was first discovered in mushrooms and was widely found in the shells of crustaceans and arthropods, the cell walls of fungi (yeast and mold) and algae, and the mollusks. The original chitin in nature usually has an antiparallel molecular chain alignment forming nanofibers connected by inter‐ and intramolecular hydrogen bonds. These microfibers consist of nanofibers about 2‐5 nm in diameter, and about 300 nm long, embedded by protein matrices. Due to their unique dimensional, optical, mechanical, and other characteristics, the preparation of nano‐chitin materials is an important subject. It is possible to extract nano‐chitins from their sources with various methods, including acid hydrolysis, mechanical disintegration, TEMPO‐mediated oxidation, electrospinning, and others. In this article, the latest progress in recent years in the preparation and applications of nano‐chitin were reviewed. The morphology of the nano‐chitins obtained from the above methods was presented. The advantages and disadvantages of each method were analyzed. An overview of applications of nano‐chitins was discussed, including biomedicine, food applications, water treatment, green electronic materials, enzyme immobilization carriers, cotton textile materials, cosmetics, and others. Abstract : Chitin is widely found in nature. The raw chitin can be treated by a series of various methods to obtain different forms of nano‐chitin, which has a good application prospect in many fields.